Boosting electrocatalytic hydrogen evolution with anodic oxidative upgrading of formaldehyde over trimetallic carbides - Du, Xiangbowen (2022)
Coupling the electrochemical oxidative upgrading of organic molecules with hydrogen evolution reaction could enable the energy-efficient production of H2 from renewable electricity with simultaneous chemical production. This work shows that a trimetallic carbide (Co3Fe3W6C), derived from one-pot synthesis, could act as a robust electrocatalyst for formaldehyde upgrading reaction (FUR) to produce formate at a high faradaic efficiency (>98%), without any production of CO2 or O2. Compared to OER, the input voltages of Co3Fe3W6C-catalyzed FUR are 150 and 120 mV lower to achieve current densities of 10 and 50 mA cm-2, respectively, thereby facilitating a significant boost in the energy efficiency of electrochemical H2 production from water. Density functional theory calculations reveal that the trimetallic carbide system modulates the d band of the transition-metal active sites to achieve optimal adsorption toward the selective oxidation of formaldehyde, while suppressing the further formation of CO2. Co3Fe3W6C was also found to be highly stable under considerably high-throughput electrochemical conditions in an alkaline electrolyte. This work offers a new strategy of synergizing water electrolysis with the oxidative upgrading of organic molecules to simultaneously boost the cost competitiveness of green hydrogen production and the electrochemical upgrading of organic feedstocks.